2013
DOI: 10.1021/jp406016z
|View full text |Cite
|
Sign up to set email alerts
|

Nanosized CoO Films on the α-Al2O3 (0001) Surface: A Density Functional Study

Abstract: The structural and magnetic properties of ultrathin CoO films supported on α-Al2O3(0001) surface are investigated on the basis of density functional theory calculations. By examining both stoichiometric and nonstoichiometric submonolayer structures at an atomic level we establish that the preferred surface arrangements are stabilized by the presence of a sublayer of O adatoms, even at the expense of creating O vacancies at the subsurface layer. Further addition of oxygen to this thin CoO layer fills the vacanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…In general, all the spectra have a similar lineshape, showing a main peak located at a binding energy around 782.0 eV and a satellite around 787.0 eV, although for the Al 2 O 3 substrate, the spectra appear slightly shifted toward lower binding energies. This difference could be due to a charge transfer of around 1 eV from the Al 2 O 3 substrate to the CoO overlayer as calculated by density functional theory elsewhere . These spectra correspond to CoO (Co 2+ ) species as reported in the literature .…”
Section: Resultssupporting
confidence: 60%
“…In general, all the spectra have a similar lineshape, showing a main peak located at a binding energy around 782.0 eV and a satellite around 787.0 eV, although for the Al 2 O 3 substrate, the spectra appear slightly shifted toward lower binding energies. This difference could be due to a charge transfer of around 1 eV from the Al 2 O 3 substrate to the CoO overlayer as calculated by density functional theory elsewhere . These spectra correspond to CoO (Co 2+ ) species as reported in the literature .…”
Section: Resultssupporting
confidence: 60%
“…The chemical potential of a supported CoO NC can be compared with that of a supported Co NC semiquantitatively using eqs and based on eq : First, the value of γ supp is the same in both eqs and ; second, we estimate that γ Co ≈ 0.65γ CoO , and third, it is assumed that molar volumes for bulk Co and CoO phases are approximately equal (Ω Co ≃ Ω CoO ). It has been shown that CoO forms a strong chemical bond to the support surface, while Co NCs interact chemically much less strongly . Consequently, γ CoO‑supp is expected to be substantially lower than γ Co‑supp because CoO is highly compatible with the support oxide surface; indeed, CoO wets the support surface, while Co 0 has a limited contact area with the support.…”
Section: Effects Of Process Conditions On Sintering Rate and Mechanis...mentioning
confidence: 99%
“…First, the value of γ supp is the same in both eqs 31 and 32; second, we estimate that γ Co ≈ 0.65γ CoO , and third, it is assumed that molar volumes for bulk Co and CoO phases are approximately equal (Ω Co ≃ Ω CoO ). It has been shown that CoO forms a strong chemical bond to the support surface,234 while Co NCs interact chemically much less strongly 12. Consequently, γ…”
mentioning
confidence: 99%
“…However, very little is known about the magnetism of zinc blende‐CoO . Although its magnetic properties have not been elucidated experimentally, theoretical studies predict an antiferromagnetic order . Concerning wurtzite‐CoO, more systematic studies have only recently been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Although its magnetic properties have not been elucidated experimentally, theoretical studies predict an antiferromagnetic order. [13,14] Concerning wurtzite-CoO, more systematic studies have only recently been carried out. In particular, wurtzite-CoO has been found to be rather stable in nanoparticle form [15][16][17][18][19] and has been reported to have appealing catalytic, optical, semiconducting, electrochemical, and biomedical properties, [20][21][22][23][24][25][26] with possible applications in lithium batteries, [27] solar energy conversion, [28] photoacoustic imaging, [24,27] and water splitting.…”
mentioning
confidence: 99%